TOPICAL DILTIAZEM OINTMENT FOR POST-HEMORRHOIDECTOMY PAIN - Abidi, Syeda Sakina; Bakhtiar, Nighat; Kerawala, Asad Ali; Awan, Saima (Journal of Ayub Medical College Abbottabad, 2021)
Background: Hemorrhoids are one of the most common anal pathology affecting millions of people around the world. Milligan-Morgan open hemorrhoidectomy is the most effective hemorrhoidectomy method used as gold standard procedure. Post-operative pain is recognized as a distressing complication of hemorrhoidectomy leading to increase hospital stay and psychological stress to both patient and surgeon. This study is designed to determine the efficacy of diltiazem gel in relieving pain after hemorrhoidectomy caused by anal muscle spasm. This will lead to decreased hospital stay and save both patient and surgeon from stress in postoperative period. Objective: To compare mean post-operative pain in patients undergoing hemorrhoidectomy with vs. without topical application of diltiazem gel. Methods: Total 80 patients who were diagnosed with third- and fourth-degree hemorrhoids and undergo hemorrhoidectomy were included in the study. Patients were randomly allocated to two groups using opaque sealed envelope method. Group A and B both have 40 patients in each group. Pain score was measured on visual analogue scale (VAS) by asking the patients to fill a questionnaire or by the help of the doctor. Results: The patient’s average age was 39.98±7.98 years. At 24 hours, mean pain score was significantly high in group B than group A [7.23±0.95 vs. 5.38±1.06; p=0.0005]. At 3rd post-operative day, mean pain score was significantly high in group B than group A [5±0.78 vs. 3.08±0.99; p=0.0005]. Seventy percent cases were observed in group B which required rescue analgesia. Conclusion: It is concluded that application of diltiazem ointment at perianal area with standard treatment considerably decreases pain after haemorrhoidectomy. Keywords: Hemorrhoids; Hemorrhoidectomy; Diltiazem gel